TRAINING AND PROFESSIONAL VOLUNTEER ORGANIZATIONS - V. A. STARODUBTSEV; P. V. RODIONOV (Высшее образование в России)
Participation of young generation in volunteer organizations is a measure of positive civic activity having the personal value meaning. The article gives the classification of volunteer organizations in the Russian Federation in scope, areas and period of activity, provides a taxonomy of objectives and general principles of the volunteer community. The authors highlighte the role of the training and professional volunteer organizations affiliated with educational institution and used for students’ professional probation in addition to academic learning. The paper defines the organizational and pedagogical conditions for successful activity of a volunteer organization, describes the experience of Jurginsky Institute of Technology in organizing the activities of the training and professional volunteer organization.